2008
DOI: 10.1096/fj.08-107169
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis induces expression of sphingosine kinase 1 to release sphingosine‐1‐phosphate as a “come‐and‐get‐me” signal

Abstract: Sphingosine-1-phosphate (S1P) is a bioactive lipid that regulates myriad important cellular processes, including growth, survival, cytoskeleton rearrangements, motility, and immunity. Here we report that treatment of Jurkat and U937 leukemia cells with the pan-sphingosine kinase (SphK) inhibitor N,N-dimethylsphingosine to block S1P formation surprisingly caused a large increase in expression of SphK1 concomitant with induction of apoptosis. Another SphK inhibitor, D,L-threo-dihydrosphingosine, also induced apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
244
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(259 citation statements)
references
References 56 publications
8
244
0
3
Order By: Relevance
“…However, it is important to note that it was never directly shown that S1P from the apoptotic supernatants was the chemotactic factor. In addition, the authors showed that there was no increase in extracellular SphK1, 33 suggesting that the S1P generation occurred within a cell. However, they did not rule out any actions of SphK2 as it has since been shown to be secreted during apoptosis in a caspase-dependent manner, possibly leading to extracellular generation of S1P.…”
Section: Steps Involved In Clearancementioning
confidence: 98%
See 1 more Smart Citation
“…However, it is important to note that it was never directly shown that S1P from the apoptotic supernatants was the chemotactic factor. In addition, the authors showed that there was no increase in extracellular SphK1, 33 suggesting that the S1P generation occurred within a cell. However, they did not rule out any actions of SphK2 as it has since been shown to be secreted during apoptosis in a caspase-dependent manner, possibly leading to extracellular generation of S1P.…”
Section: Steps Involved In Clearancementioning
confidence: 98%
“…It had already been shown that apoptotic cells can release S1P, 32 but its function as a lipid-attraction signal during cell death was not reported until 2008. Gude et al 33 suggested that sphingosine kinase 1 (SphK1) was upregulated during apoptosis and, in turn, led to the increased secretion of S1P. Concomitantly, purified S1P was able to induce phagocyte chemotaxis.…”
Section: Steps Involved In Clearancementioning
confidence: 99%
“…Considering that AC release S1P (Weigert et al, 2006;Gude et al, 2008) and the further notion that S1P potentially causes HO-1 expression (Man et al, 2005), we assumed that S1P in AC-CM was responsible for HO-1 expression in macrophages. To verify this hypothesis, we stimulated primary human macrophages with authentic S1P for 24 h ( Figure 2A).…”
Section: S1p In Ac-cm Is Crucial In Provoking Ho-1 Inductionmentioning
confidence: 99%
“…42 Adding methylpyruvate stimulates ATP production and restores the externalization of phosphatidylserine in autophagy-defective cells, suggesting that autophagy maintains the level of ATP under these conditions. 42 Interestingly sphingosine 1-phosphate, which is known to stimulate autophagy, 43 is secreted by dying cells 44 and has been identified as a 'come and get me' signal. These findings highlight the importance of autophagy in ensuring a clean death process by favoring the elimination of apoptotic bodies.…”
Section: Autophagy and Apoptosismentioning
confidence: 99%